Automatic Enhancement Of Digital Images Using Cubic Bézier Curve And Fourier Transformation - Asghar, Khurshid; Gilanie, Ghulam; Saddique, Mubbashar; Habib, Zulfiqar (Malaysian Journal of Computer Science, 2017)
Image enhancement is one of the most important and visually appealing areas of digital image processing and computer vision. It is considered as a very important part of pre-processing for the development of industrial, security, forensic, medical, and many other applications. Although significant efforts were devoted in the past, a completely automatic image enhancement for all types of input and applications is still a big challenge in the domain of image processing. In this paper, we have proposed a multi-disciplinary approach to enhance the image automatically by intensity transformation in the spatial domain through cubic Bézier curve on images filtered with low and high pass Butterworth in the frequency domain. Results are promising when compared with the existing state-of-the-arts techniques for both visually and quantitatively, which proved that the proposed method can ensure better contrast enhancement.